Answer :

Answer:

x = - [tex]\frac{1}{4}[/tex]

Step-by-step explanation:

To find f(g(x)) substitute x = g(x) into f(x), that is

f(g(x))

= f(x + 1)

= 2(x + 1)² ← expand using FOIL

= 2(x² + 2x + 1) ← distribute

= 2x² + 4x + 2

To find g(f(x)) substitute x = f(x) into g(x), that is

g(f(x))

= g(2x²)

= 2x² + 1

----------------------------------------------------------

Equating  gives

2x² + 4x + 2 = 2x² + 1 ( subtract 2x² + 1 from both sides )

4x + 1 = 0 ( subtract 1 from both sides )

4x = - 1 ( divide both sides by 4 )

x = - [tex]\frac{1}{4}[/tex]

Other Questions